Between you & me [compact disc, unabridged] : confessions of a Comma Queen - Norris, Mary, 1952- (Recorded Books, LLC, 2015)
Mary Norris has spent more than three decades guarding The New Yorkers grand traditions of grammar and usage. Now she offers her vast experience in a charming language book as full of life as it is of practical advice.